2023
DOI: 10.1021/acs.chemmater.3c00537
|View full text |Cite
|
Sign up to set email alerts
|

A First-Principles Explanation of the Luminescent Line Shape of SrLiAl3N4:Eu2+ Phosphor for Light-Emitting Diode Applications

Abstract: White light-emitting diodes are gaining popularity and are set to become the most common light source in the U.S. by 2025. However, their performance is still limited by the lack of an efficient red-emitting component with a narrow band emission. The red phosphor SrLiAl3N4:Eu2+ is among the first promising phosphors with a small bandwidth for next-generation lighting, but the microscopic origin of this narrow emission remains elusive. In the present work, density functional theory, the ΔSCF-constrained occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…We assume that Eu 2+ is distributed on two crystallographically distinct sites in Sr[Li 3 (Al/Ga)O 4 ]. A comparable situation exisits for Sr[LiAl 3 N 4 ]:Eu 2+ , where time-resolved and low-temperature luminescence spectroscopy at T = 10 K were used to decompose the virbronic structure of the emission transitions, revealing that Eu 2+ occupies two crystallographically distinct strontium sites. , The luminescence of the single crystals used for the structure determinations of the title compounds were investigated and the normalized emission spectra of the Eu 2+ -activated compounds are shown in Figure S3. Peak wavelengths were observed at λ em = 568 nm with a fwhm equals 46 nm for Sr[Li 3 AlO 4 ]:Eu 2+ and at λ em = 552 nm with a fwhm equals 48 nm for Sr[Li 3 GaO 4 ]:Eu 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that Eu 2+ is distributed on two crystallographically distinct sites in Sr[Li 3 (Al/Ga)O 4 ]. A comparable situation exisits for Sr[LiAl 3 N 4 ]:Eu 2+ , where time-resolved and low-temperature luminescence spectroscopy at T = 10 K were used to decompose the virbronic structure of the emission transitions, revealing that Eu 2+ occupies two crystallographically distinct strontium sites. , The luminescence of the single crystals used for the structure determinations of the title compounds were investigated and the normalized emission spectra of the Eu 2+ -activated compounds are shown in Figure S3. Peak wavelengths were observed at λ em = 568 nm with a fwhm equals 46 nm for Sr[Li 3 AlO 4 ]:Eu 2+ and at λ em = 552 nm with a fwhm equals 48 nm for Sr[Li 3 GaO 4 ]:Eu 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The interconfigurational transitions from the excited 4f 6 5d 1 states to the 4f 7 ground state of the Eu 2+ activator ion in the above-mentioned compounds lead to narrow-band emissions in the red spectral region of the visible spectrum, making some of them promising candidates for applications in phosphor-converted light-emitting diodes (pc-LEDs) . In the cases of Ca[LiAl 3 N 4 ], Sr[LiAl 3 N 4 ] and Sr[Li 2 Al 2 O 2 N 2 ], detailed spectroscopic studies have been carried out to explore the coordination environments of Eu 2+ . Except for Ca 18.75 Li 10.5 [Al 39 N 55 ] and Sr 4 [LiAl 11 N 14 ], the crystal structures of the described oxo(nitrido)lithoaluminates are ordered variants of the U[Cr 4 C 4 ] aristotype . The rediscovery of the U[Cr 4 C 4 ]-type structure or closely related structures was driven by the observation of (ultra-) narrow-band emissions emanating from Eu 2+ -activated alkaline-rich lithosilicates and alkaline earth-rich lithoaluminates. ,, The nitridolithoaluminate Sr[LiAl 3 N 4 ] crystallizes in the ordered variant, which was first described for the isotypic crystal structure of Cs[Na 3 PbO 4 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Hence while at room temperature within the experimental resolution, the two sites provide similar absorption spectra and emission spectra, 1 it has been recently shown that at low temperature, they provide unique emission band signatures in the vibrationally resolved emission spectrum. 58 These phosphors define the lower and upper boundaries of a range of Eu 2+ doped phosphors in which the crystal field strength as well as the Eu/ML 8 cuboid compression is increasing. 1 It should be noted that the actual bottom boundary in the Eu 2+ -doped phosphors is defined by the narrow band red emitting Ca[LiAl 3 N 4 ]:Eu 2+ (CLA:Eu 2+ ) phosphor.…”
Section: Experimental Spectramentioning
confidence: 99%
“…38,52–54 This approach opens new avenues for investigating and optimizing the emission properties of Eu-doped phosphors, ultimately leading to improved performance. In systems with multiple potential doping centers, aspects like the volume of the doping coordination region, 3 the probability of doping and the vibronic coupling of the rigid host structure 55–58 have been successfully employed to interpret the studied phosphor emission properties. In particular, they have been employed to provide insight over the nature of the emission band in room and low temperature spectra of RbNa[Li 3 SiO 4 ] 2 :Eu 2+ 55 and Sr[LiAl 3 N 4 ]:Eu 2+ 58 or to understand the relationship of the host environment to the heat induced blue shift (HIB) phenomenon in Eu 2+ -doped phosphors.…”
Section: Introductionmentioning
confidence: 99%